Stimulation of human endothelial cell prostacyclin synthesis by select leukotrienes (The Rockefeller University Press, 1984)
Cultured endothelial cells from human umbilical cord labeled with [3H]20:4 release radiolabel when exposed to leukotrienes C or D (LTC or LTD). The major radiolabeled 20:4 metabolite recovered in the culture medium was prostacyclin. Both leukotrienes produced a dose-dependent synthesis of prostacyclin, with a maximal response at 10(-7) M leukotriene. LTC promoted a twofold greater response than did LTD at all concentrations tested (10(-9) to 10(-7) M). In contrast, no release of radiolabel above basal levels was evident with a challenge of LTE or LTB at the same concentrations. Endothelial cells metabolize approximately 40-50% of exogenously supplied LTC to LTD and LTE in 60 min. Levels of alpha-glutamyltranspeptidase (gamma-GTPase), the ectoenzyme reported to convert LTC or LTD, were detected in intact endothelial cells with the chromogenic substrate L-gamma-glutamyl-p- nitroanilide at levels sufficient to account for the observed rate of LTC metabolism. High concentrations of the gamma-GTPase inhibitors, glutathione and AT-125, blocked the metabolism of LTC by endothelium. These results suggest that degradation of leukotrienes by endothelium may be one mechanism for inactivation of these lipid mediators.